Empowering Rural Communities through Village-Owned Enterprise Strategies - Budi Wulandari; Yudan Hermawan; Kiki Irafa Candra (Education and Sociedad Journal, 2026)
This study reports on a community engagement program aimed at strengthening the role of Village-Owned Enterprises (BUMDes) in empowering communities in the village. The program employed a participatory and action-oriented approach involving 25 participants, including village officials, BUMDes managers, and community members. The program was conducted over three months through four main stages: initial assessment, program design, implementation (training, workshops, and mentoring), and evaluation. Initial findings revealed several key constraints, including the absence of standard operating procedures (SOPs), limited managerial capacity (only 2 of 8 managers were able to prepare basic financial records), low community participation (fewer than 10 active participants), and stagnant business activities. Following the intervention, measurable improvements were observed. A basic SOP document was developed, 7 of 8 managers were able to prepare simple financial reports, a draft business plan was produced, and community participation increased to approximately 18–20 people. In addition, two new potential business ideas were identified, and improvements were noted in the management of existing business units. This study suggests that effective BUMDes development should prioritize simple governance mechanisms, applied capacity building, and inclusive community engagement. Insights from this program provide practical implications for village governments and policy makers in improving community-based economic institutions.